Government of Plateau State of Nigeria, 1992 approved budget - Plateau State of Nigeria (Jos: Government of the Plateau State of Nigeria, 1992)
This budget was tagged -Transition Budget of the plateau state government
osc 15/04/2019
Arch
Keywords: Budget; Expenditure, public; Plateau State, Nigeria